Analisis Faktor yang Memengaruhi Masa Tunggu Kerja Pertama Lulusan FMIPA Universitas Sriwijaya - Yolanda, Defita; Maiyanti, Sri Indra; Faruk, Alfensi (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The waiting time for graduates to find employment is a vital indicator of the relevance of higher education to the labor market, but the factors influencing the waiting time for graduates of the Faculty of Mathematics and Natural Sciences (FMIPA) at Sriwijaya University (Unsri) have not yet been studied in depth. This research aims to analyze the factors influencing the waiting time for employment of Unsri graduates. Using the data from the tracer study conducted, a sample size of 110 alumni from the Faculty of Mathematics and Natural Sciences (FMIPA) at Sriwijaya University (Unsri) was obtained. This study applies the ordinal logistic regression method to model the categorical data structure of the ordinal response variable. Based on the analysis conducted, it is evident that the factors influencing FMIPA Unsri alumni in obtaining their first job (p-value < 0.1) are gender, year of graduation, study program, and the job title applied for.